Temperature-Driven Optimization of LiCoO2 Thin-Film Cathodes via Pulsed Laser Deposition: Structural and Morphological Control - Ayu, Nur Ika Puji; Rivai, Abu Khalid; Evvy, Kartini (Research Center of Inorganic Materials and Coordination Complexes, FMIPA Universitas Sriwijaya, 2025)
Thin LiCoO2 film cathodes were fabricated on silicon substrate by Pulsed Laser Deposition (PLD). The microstructural properties were investigated as a function of the substrate temperature (Ts), which varied between 750◦C, 850 ◦C and 900 ◦C. The deposition was performed using Nd:YAG laser (266 nm, 100 mJ) under an oxygen partial pressure of 200 mTorr. X-ray Diffraction (XRD) analysis revealed that films consist of HT-LiCoO2 and a small amount of Co3O4 precipitates. The highest crystallinity was obtained for the thin film deposited at Ts = 900 ◦C, whereas the Atomic Force Microscopy (AFM) indicated uniform grain size distributions of the film deposited at Ts = 850 ◦C with an approximate surface roughness of 18 nm. The increase of surface roughness at higher Ts was attributed to non-uniform grain distribution, highlighting the importance of substrate temperature control in minimizing interfacial defects for improved electrochemical performance. This study provides key insights into the interplay between PLD parameters and film microstructure, offering a pathway for optimizing LiCoO2 cathodes for thin-film batteries and advanced solid-state energy storage devices.